Given the function \( f(x)=4 x-4 \), evaluate and simplify the expressions below. See special instructions on how to enter your answers. \( f(a)= \) \( f(a+h)= \) \( \frac{f(a+h)-f(a)}{h}=\square \) lnstructions: Simplify answers as much as possible. Expressions such as \( 4(x+2) \) and \( (x+5)^{2} \) should be expanded. Also collect like terms, so \( 3 x+x \) should be written as \( 4 x \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To evaluate the function \( f(x) = 4x - 4 \): 1. For \( f(a) \): \[ f(a) = 4a - 4 \] 2. For \( f(a+h) \): \[ f(a+h) = 4(a+h) - 4 = 4a + 4h - 4 \] 3. Now, calculating \( \frac{f(a+h) - f(a)}{h} \): \[ \frac{f(a+h) - f(a)}{h} = \frac{(4a + 4h - 4) - (4a - 4)}{h} \] Simplifying the numerator: \[ \frac{4a + 4h - 4 - 4a + 4}{h} = \frac{4h}{h} \] Therefore: \[ \frac{f(a+h) - f(a)}{h} = 4 \] So the simplified answers are: - \( f(a) = 4a - 4 \) - \( f(a+h) = 4a + 4h - 4 \) - \( \frac{f(a+h) - f(a)}{h} = 4 \)